The Determinants of Invention in Electricity Generation Technologies A Patent Data Analysis - Lanzi, Elisa (OECD Environment Working Papers, 2012)
This paper analyses the determinants of invention in efficiency-enhancing electricity generation technologies that have the potential to facilitate climate change mitigation efforts, including fossil fuelbased technologies aimed at reducing carbon emissions, renewables and nuclear technologies. The evolution of inventive activity in these technologies is analysed by considering patent data for 11 OECD countries over the period 1978-2008. The analysis considers various drivers of inventive activity, including R&D expenditures and electricity consumption, but pay particular attention to the role of fossil fuel prices because they suggest the impact that price mechanisms such as emissions trading and carbon taxes are likely to have on invention in the electricity generation sector. The results show that the effect of fossil fuel prices varies according to the different types of technologies. As fossil fuel prices increase, inventive activity in renewable energy technologies increases while the effect of on fossil fuel-based technologies is positive but with decreasing increments. The results show that there is no effect of fossil fuel prices on patenting activity in nuclear energy technologies. These results illustrate that there may be a price-induced switching between renewable and fossil fuel-based technologies. As fossil fuel prices rise, an efficiency effect encourages inventive activity in both fossil fuelbased and renewable technologies. As fossil fuel prices increase further, invention in fossil fuel-based technologies starts declining suggesting that a substitution effect drives away innovation from fossil fuelbased towards renewable energy technologies